The Effect of Macroeconomic Variables on the Profitability of Islamic Commercial Banks in Indonesia - Huda, Miftahul; Rofiqo, Azidni; Abdul Razak, Abdurrizqi Bin; Nabila, Fikriyyatun (Islamic Economics Journal, 2024)
Islamic banks as a form of banking that operates based on sharia principles, are expected to show superior financial performance when compared to interest-based conventional banks. This study aims to determine the effect of inflation, JUB, and PUAS on the profitability of Indonesian Islamic Commercial Banks. The method used in this research is a deductive quantitative method, with the Vector Autoregressive (VAR) Vector Error Correction Model (VECM) approach and the E-Views 12 test tool. The data used in this study used secondary data with time series data from the period January 2013 to April 2023, where ROA was used as an independent variable and Inflation, Money Supply, and Islamic Interbank Money Market became the dependent variable. As for the results of this study, in the long term, the variables of Inflation and JUB have a significant and negative effect on the Return on Assets (ROA) of Indonesian Islamic Commercial Banks, while the Islamic Interbank Money Market (PUAS) variable does not have a significant and negative effect on the Return on Assets (ROA) of Indonesian Islamic Commercial Banks. In the short term, the variables of Inflation, Money Supply (JUB), and the Islamic Interbank Money Market (PUAS) do not have a significant and negative influence on the Return on Assets (ROA) of Indonesian Islamic Commercial Banks.